2019
DOI: 10.1186/s41239-019-0163-0
|View full text |Cite
|
Sign up to set email alerts
|

MOOC-based flipped learning in higher education: students’ participation, experience and learning performance

Abstract: Relying on advanced network technologies, Massive Open Online Courses (MOOCs) can support the transformation and deep construction of high-quality open courses. However, with the use of MOOCs in many universities and colleges, new issues have emerged. MOOCs are not specifically designed for local conditions. Researchers lack understanding of the effectiveness of using shared MOOCs in traditional university teaching. The purpose of this study was to analyze the effectiveness of MOOC-based flipped learning and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 48 publications
6
79
1
6
Order By: Relevance
“…The results of one-way covariance analysis and mean differences showed that education based on flipped learning on the academic achievement of sixth-grade elementary school students in Lamerd has had a positive and significant effect. The present study was consistent with the research of Nemati (2019), Kaviani et al (2018), Nam (2019), Choi (2019), Eryilmaz and Cigdemoglu (2019) and Wang and Zhu (2019) . Due to the novelty of the flipped training method on the one hand and the special importance of the variable of academic achievement on the other hand, many pieces of research have been or are being done in this field inside and outside the country.…”
Section: Discussionsupporting
confidence: 93%
“…The results of one-way covariance analysis and mean differences showed that education based on flipped learning on the academic achievement of sixth-grade elementary school students in Lamerd has had a positive and significant effect. The present study was consistent with the research of Nemati (2019), Kaviani et al (2018), Nam (2019), Choi (2019), Eryilmaz and Cigdemoglu (2019) and Wang and Zhu (2019) . Due to the novelty of the flipped training method on the one hand and the special importance of the variable of academic achievement on the other hand, many pieces of research have been or are being done in this field inside and outside the country.…”
Section: Discussionsupporting
confidence: 93%
“…Educational data mining and state-of-the-art There has been a lot of progress in the current literature about using data obtained from the educational settings to improve the intended processes (Wang & Zhu, 2019;Abu Zohair, 2019, Exter et al, 2019Munro, 2018;Dommett, Gardner, & van Tilburg, 2019;Alizadeh, Mehran, Koguchi, & Takemura, 2019). It is noteworthy that existing research has demonstrated that HEIs are increasingly datahungry, with the stakeholders (students, teachers, and administrators, for example) seeking data and study results for their own needs and use (Clark, 2015;Williamson, 2018).…”
Section: Conceptualizing Text Mining For Teaching and Learning Assessmentioning
confidence: 99%
“…These include (a) engagement in technological ALEs that emphasize in-class collaboration among STEM undergraduate students (Bernard et al, 2014;National Science and Technology Council, 2013); (b) engagement in technological ALEs that incorporate two settings, specifically the FC and the PBL approaches for active learning (DeLozier & Rhodes, 2017;National Research Council, 2012;Reis et. al., 2018); and (c) investigation of various cognitive and affective aspects of STEM undergraduate learning experiences, including performance and perceptions Wang & Zhu, 2019).…”
Section: Conclusion and Contributionsmentioning
confidence: 99%
“…Students learn actively, practice a student-centered approach, and receive feedback from their instructors. This combination has been shown to increase students' learning satisfaction (Baepler, Walker, & Driessen, 2014;Jensen, Kummer, & Godoy, 2015;Wang & Zhu, 2019).…”
Section: Introductionmentioning
confidence: 99%